Adriamycin cardiotoxicity: report of an unusual case with features resembling endomyocardial fibrosis. Issue 6 (June 1981) - Fitter, W; deSa, D J; Pai, K R
Abstract : We report on a case of adriamycin cardiotoxicity occurring in a five-year-old boy treated for rhabdomyosarcoma. In addition to the usual features of myofibrillary degeneration associated with adriamycin, extreme endocardial fibrosis and mural thrombosis affecting the apical segments of both ventricles but particularly the left ventricle was seen at necropsy. The changes resembled classical endomyocardial fibrosis.